Didactic Conditions of Implementing the Process of Preparing Future Vocational Education Teachers for Computer Modeling - Dadaboyeva Zulhumor Matkarim qizi (International Journal on Integrated Education, 2022)
In this article, the didactic conditions for the implementation of the process of preparing future vocational teachers for computer modeling were studied.